FITC and Ru(phen)3 2+ co-doped silica particles as visualized ratiometric pH indicator - Sun Lei; Zhang Huimao; Xu Jianquan; Li Jun; Liang Jinglun; Yang Wensheng (Nanoscale Research Letters, 2011)
Abstract The performance of fluorescein isothiocyanate (FITC) and tris(1, 10-phenanathroline) ruthenium ion (Ru(phen)3 2+) co-doped silica particles as pH indicator was evaluated. The emission intensity ratios of the pH sensitive dye (FITC) and the reference dye (Ru(phen)3 2+) in the particles were dependent on pH of the environment. The changes in emission intensity ratios of the two dyes under different pH could be measured under single excitation wavelength and readily visualized by naked eye under a 365-nm UV lamp. In particular, such FITC and Ru(phen)3 2+ co-doped silica particles were identified to show high sensitivity to pH around the pKa of FITC (6.4), making them be potential useful as visualized pH indicator for detection of intracellular pH micro-circumstance.